Blended Teaching Practices for Active Learning in Higher Pharmacy Education - Liu, Wenyuan; Gao, Xinzhu; Han, Lingfei; Liu, Jing; Feng, Feng (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Blended adoption of active learning practices improves student achievement on average in college. Nevertheless, there have been few studies to date on the effects of detailed factors on learning outcomes. Objectives: The aim of this study was to develop a blended teaching strategy by incorporating methods of team-based learning (TBL) and e-learning into a Pharmaceutical Analysis course for student active learning, and to explore how the practice impacts student learning outcomes. Materials and Methods: Two blended teaching programs with different blending ratios of TBL and e-learning methods were developed and compared in this study. Students from four experimental classes enrolled in three majors were recruited. Student outcomes related to active learning goals were evaluated using formative and summative evaluation methods. A survey administered after the study was completed. Results: Student e-learning performance was positively correlated with the final scores, suggesting that exercises and tests provided by the e-learning platform made a positive contribution to student knowledge achievement. On surveys a large majority of students reported that working on instructor-posed questions in a TBL setting improved their higher-order cognitive skills, social cohesion and, through that, feelings of accountability. Final scores showed significant differences among students from different majors, which implied that the effectiveness of active learning depends on the characteristics of students and their activities outside of class. Conclusion: The blended teaching strategy developed in this study was effective in improving student achievement in either formative or summative assessments, which provides an accessible and informative entry point for implementing active learning in higher pharmacy education.
Keywords: Higher pharmacy education; Blended teaching; Active learning; E-learning; Team-based learning